2009
DOI: 10.2488/jwrs.55.299
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Porous Bamboo Carbon by Low-Temperature Activation in Air

Abstract: Bamboo carbon was prepared in N 2 flow for 2 hours at 500 C with heating rates from 7 C/min to 39 C/min, resulting in a BET surface area ranging from 28 to 252 m 2 /g, respectively. For the next step, the pore structure of the bamboo carbon was developed by air oxidation at 280 C for 2 hours, comparing it with coconuts shell char activation. A BET surface area of 460 m 2 /g could be achieved for the bamboo carbon, but only 230 m 2 /g for the coconuts shell char. When the air oxidation was conducted after de-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…They suggested that the reason is the high amount of the content based on wood, which is easy to thermal decomposition. The wood mainly contains cellulose, hemicellulose and lignin have the wide range of thermal decomposition (160-450°C ) [20]. In this study, we evaluated the thermal properties by TG-DTA system (DTG-60, Shimazu Corporation, Japan).…”
Section: Thermal Stability Of the Epoxy Resins Based On Liquefied Woodmentioning
confidence: 99%
“…They suggested that the reason is the high amount of the content based on wood, which is easy to thermal decomposition. The wood mainly contains cellulose, hemicellulose and lignin have the wide range of thermal decomposition (160-450°C ) [20]. In this study, we evaluated the thermal properties by TG-DTA system (DTG-60, Shimazu Corporation, Japan).…”
Section: Thermal Stability Of the Epoxy Resins Based On Liquefied Woodmentioning
confidence: 99%
“…The ash content of a coconut shell is much lower than that of SCG or bamboo, 10 which is why activated carbon derived from coconut shells offers a superior performance.…”
Section: Introductionmentioning
confidence: 99%
“…We therefore focused our attention on the low temperature air oxidation method [2]. This method involves air oxidation at a lower temperature of 300°C or less without chemical treatment or gas influx, and thus it enables treatment in a shorter timeframe and at a lower cost when compared to the other methods.…”
Section: Introductionmentioning
confidence: 99%